Ayurveda preventive measure for environmental toxicity induced skin disease and its management - chandel, Vandana; Sharma, Anita; yadav, Seema (International Research Journal of Ayurveda & Yoga, 2020)
Natural toxicant incites Skin illness has been expanded in India. The toxicant transmitted from air contamination and it has been influenced to person. The air contamination like Sulfur dioxide (SOx), Carbon monoxide (CO), Nitrogen oxides ( NOx) are blended into the air making it harmful what’s more, it uses for showering bug splash,pesticides like DDT, Ayurveda is an out of date clinical science and referenced air poison like Atidhup savan ,sheet-ushna parivartan as causative segments of skin affliction including extreme touchiness, Mukhdhushika ,Vicharchika ,Pama .This evasion and the administrators of disease is the basic rule of Ayurveda for any sickness. Ayurveda suggested the nidan parivarjan for avoiding of such kind of disease causing and its irritating parts,After realization of samsarjana karma Patolmooladikwath, Mustadichurna, Triphaladichurna, Madhavasava, Kanakabindvarista, Triphalasava, Sulphur of mercury.